MitoTEMPO Prevents Oxalate Induced Injury in NRK-52E Cells via Inhibiting Mitochondrial Dysfunction and Modulating Oxidative Stress. (2nd January 2017) - Zhang, Jiaqiao; Wang, Qing; Xu, Chuou; Lu, Yuchao; Hu, Henglong; Qin, Baolong; Wang, Yufeng; He, Deng; Li, Cong; Yu, Xiao; Wang, Shaogang; Liu, Jihong
Abstract : As one of the major risks for urolithiasis, hyperoxaluria can be caused by genetic defect or dietary intake. And high oxalate induced renal epithelial cells injury is related to oxidative stress and mitochondrial dysfunction. Here, we investigated whether MitoTEMPO, a mitochondria-targeted antioxidant, could protect against oxalate mediated injury in NRK-52E cells via inhibiting mitochondrial dysfunction and modulating oxidative stress. MitoSOX Red was used to determine mitochondrial ROS (mtROS) production. Mitochondrial membrane potential (Δ ψ m) and quantification of ATP synthesis were measured to evaluate mitochondrial function. The protein expression of Nox4, Nox2, and p22 was also detected to explore the effect of oxalate and MitoTEMPO on NADPH oxidase. Our results revealed that pretreatment with MitoTEMPO significantly inhibited oxalate induced lactate dehydrogenase (LDH) and malondialdehyde (MDA) release and decreased oxalate induced mtROS generation. Further, MitoTEMPO pretreatment restored disruption of Δ ψ m and decreased ATP synthesis mediated by oxalate. In addition, MitoTEMPO altered the protein expression of Nox4 and p22 and decreased the protein expression of IL-6 and osteopontin (OPN) induced by oxalate. We concluded that MitoTEMPO may be a new candidate to protect against oxalate induced kidney injury as well as urolithiasis.